PENGARUH PAJAK DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN SAROLANGUN - M Zahari (Universitas Batanghari Jambi, 2016)
Acceptance of local revenue (PAD) is an important revenue source for the implementation of regional autonomy. Excavation potential local taxes and local retribution optimally will be able to make a significant contribution to the increase in revenue from PAD in Sarolangun district. The purpose of this study to determine the potential of local tax revenues and levies as well as its effect on PAD Sarolangun district. This research was conducted at the Department of PPKAD Sarolangun district. The research method used descriptive qualitative method and multiple linear regression. The results showed that the potency of taxes and local retribution still low and needs to be improved. During the period of 2010-2015, the contribution of local tax revenue to the PAD an average of 23.1 % one year, and the contribution of local retribution revenue an average of 16.01% one year. Overall, local taxes and local retribution affect the PAD increase in Sarolangun district.Keywords: acceptance of local revenue, local taxes and local retribution